2013
DOI: 10.1021/ja309523t
|View full text |Cite
|
Sign up to set email alerts
|

Using TiO2 as a Conductive Protective Layer for Photocathodic H2 Evolution

Abstract: Surface passivation is a general issue for Si-based photoelectrodes because it progressively hinders electron conduction at the semiconductor/electrolyte interface. In this work, we show that a sputtered 100 nm TiO(2) layer on top of a thin Ti metal layer may be used to protect an n(+)p Si photocathode during photocatalytic H(2) evolution. Although TiO(2) is a semiconductor, we show that it behaves like a metallic conductor would under photocathodic H(2) evolution conditions. This behavior is due to the fortun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
462
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(487 citation statements)
references
References 29 publications
17
462
2
6
Order By: Relevance
“…Sun and He 9,10 used NiO x layers instead of TiO 2 , thus foregoing the need of an additional catalyst layer, and Mei 11 employed an Ir | IrO x structure instead. While Seger et al 12,13 found that a thin metal layer on the silicon prior to metal oxide deposition resulted in improved performance by reducing the oxidation of the silicon substrate.…”
mentioning
confidence: 99%
“…Sun and He 9,10 used NiO x layers instead of TiO 2 , thus foregoing the need of an additional catalyst layer, and Mei 11 employed an Ir | IrO x structure instead. While Seger et al 12,13 found that a thin metal layer on the silicon prior to metal oxide deposition resulted in improved performance by reducing the oxidation of the silicon substrate.…”
mentioning
confidence: 99%
“…49 Seger et al has used a 100 nm TiO 2 layer protection onto an n + p Si photocathode by sputter deposition method. 79 Aer annealing, the protected photocathode had a stable HER photocurrent for 72 h in 1 M HClO 4 electrolyte. Although TiO 2 is a n-type semiconductor, a metallic conductor behavior was found due to the alignment of the Si conduction band with the TiO 2 conduction band and the hydrogen evolution potential.…”
Section: Passivation Layer Stabilization Against Chemical Corrosionmentioning
confidence: 99%
“…9 Previous research has shown that when using moderately doped TiO 2 , anodic electron transfer cannot occur at potentials much more anodic H + /H 2 redox potential. 9 In Figure 3 the 5 nm Pt/n + p Si shows anodic current due It should be noted that different Si wafers were used in Figure 1 and Figure 3. Each Si wafer has a slightly different photovoltage, thus accounting for the small difference in onset potentials between Figure 1 and Figure 3.…”
mentioning
confidence: 99%
“…[6][7][8] However, the rectifying properties of this film may restrict the ability to electrodeposit catalysts onto the protected photoabsorber surface. 9,10 Even though the TiO 2 protection layer can be detrimental to certain electrodeposition procedures, it may also open up a new avenue to help improve the stability of molecular catalysts.…”
mentioning
confidence: 99%